The role of academic sport in health promotion - the example of the Academic Sports Association in Poland - Suchecki, Kajetan; Sobczyk, Karolina; Grajek, Mateusz (Journal of Education, Health and Sport, 2022)
Academic sports are physical activities in which members of the academic community participate: students, doctoral students, research, teaching or administrative staff of higher education institutions. The academic community is extremely diverse, but as a rule, it is rarely associated directly with physical activity, but rather with the advancement of knowledge and the development of science. All the more reason why the promotion of physical activity in this community is extremely important for maintaining the psychophysical well-being of members of this group. The AZS is the most numerous academic organization in Poland, with nearly 33,000 members. The Association’s Academic Championships of Poland and community leagues are the primary system of rivalry between universities in the country. Among the objectives of AZS are those relating directly or indirectly to the promotion of health, including: the dissemination of physical culture and tourism, raising physical fitness and improving health among the academic community, working for the rehabilitation of the disabled or counteracting social pathologies, particularly addictions that threaten the environment of young students. These goals are pursued through various types of programs and projects, including sports activation of the academic community within the framework of sports sections, especially within the framework of general sports, organized sports competitions both at the university, regional, national or international level. Academic sports are also often the only available opportunity for physical activity during college, where physical education classes usually last no more than a year in the five-year cycle of study.